Contribution of Co-detected Respiratory Viruses and Patient Age to the Clinical Manifestations of Mycoplasma Pneumoniae Pneumonia in Children. Issue 6 (June 2018) - Han, Mi Seon; Yun, Ki Wook; Lee, Hoan Jong; Park, Ji Young; Rhie, Kyuyol; Lee, Joon Kee; Lee, Hyunju; Kwak, Young Ho; Kim, Do Kyun; Suh, Dong In; Choi, Eun Hwa
Abstract : Background: The clinical spectrum of Mycoplasma pneumoniae pneumonia is widely variable. This study evaluated the clinical manifestations of M. pneumoniae pneumonia in children of different age groups and by the presence of co-detected respiratory virus. Methods: This study included children hospitalized with M. pneumoniae pneumonia between 2010 and 2015. At the time of pneumonia diagnosis, a nasopharyngeal aspirate was analyzed for respiratory viruses by reverse transcription-polymerase chain reaction (RT-PCR). The clinical manifestations and laboratory findings were reviewed from medical records. Results: Of the 286 children with M. pneumoniae pneumonia, 84 (29.4%) had a co-detected respiratory virus, with the highest co-detection rate in young children (51.9% of children <2 years; P = 0.002). In children <2 years, with and without co-detected virus, wheezing occurred in 35.7% and 15.4%, respectively. Among the 202 children without any virus detected, only 6.4% were <2 years. These young children showed fewer median days of fever than the children ≥2 years (8 vs. 11 days; P = 0.022). Children ≥2 years tended to have accompanying skin rashes (21.7% vs.7.7%; P = 0.310) and elevated liver enzymes (21.7% vs. 0%; P = 0.075) more frequently than children <2 years. Only 53.8% of the patients <2 years were treated with macrolide compared with 94.1% of the patients ≥2 years ( P < 0.001). Conclusions: The clinical manifestations of M. pneumoniae pneumonia in young children are milder than those in older children. A high prevalence of co-detected respiratory virus in young children suggests that virus might play a role in making pneumonia clinically apparent in this age group.